Informação e política de defesa: o debate da Defesa no Brasil após 1988 - Ceron, Angélica Behenck (2012)
This dissertation has investigated the information as a constitutive force in society in the context of the debate on defense policy in Brazil since the 1988 Constitution. The problem to be faced is how the information available on Defense subsidizes the debate of defense policy in Brazil. The proposed methodology includes the analysis of legislation and recent academic work on aspects of information policy. The changes in defense policy, as part of democratization of the Brazilian state, are studied from the point of view of information policy with a view to increasing participation in the debate. It is hoped that this research contributes to the discussion of policies and regimes of information within Information Science